Science communication for youth: RTVE in the Age of Rapid Attention: Case study of ‘Órbita Laika’ - Prieto-Arosa, Juan Manuel; Castellanos-Pineda, Patricia; Túñez-López, José Miguel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
This article examines the weak connection between Órbita Laika (RTVE) and young audiences, focusing on its digital communication strategy on TikTok and Instagram. Content analysis and digital ethnography reveal limited adaptation to platform dynamics, reliance on a linear television format, scarce interactivity, and minimal reach, resulting in a residual “ghost account” presence. These shortcomings reduce dissemination potential and hinder dialogue with Generation Z. Findings highlight the urgent need for a comprehensive renewal of the programme’s format and a participatory, cross-platform strategy prioritizing entertainment, short-form science communication, and interactive engagement to reinforce relevance, visibility, and media literacy among younger audiences in today’s rapidly evolving attention economy.